Epigenetic analysis of heat shock activator complex in the peripheral blood of Parkinson's disease patients and its clinical significance - Gemici, Yagmur Inalkac; Tasci, Irem; Dundar, Muhammed; Ozgen, Nazmi; Danis, Nefsun; Gozukara, Harika Gozde; Koc, Ahmet (Galenos Publ House, 2024)
Objectives: This study aimed to investigate the methylation changes of related genes in the peripheral blood and their clinical significance in Parkinson's disease (PD) and whether the methylation change of the gene encoding long noncoding RNA was different in the blood of patients and controls. Patients and methods: This prospective cross-sectional, controlled study was conducted with 45 participants (22 males, 23 females; mean age: 60.7 +/- 5.9 years; range, 53 to 75 years) between June 2020 and June 2021. Drug-naive patients diagnosed with PD were included in this study. Those with PD and a Mini-Mental State Examination (MMSE) score >23 were defined as Group 1 (n=15), and those with PD and an MMSE score <= 23 were defined as Group 2 (n=15). Controls were included in Group 3 (n=15). The methylation changes of genes HSP70, HSP90, heat shock factor 1 (HSF1), heat shock RNA 1 (HSR1), and eukaryotic translation elongation factor 1 alpha (eEF1a) a ) were investigated with methylation-specific real-time quantitative polymerase chain reaction analysis. Results: The eEF1a a was significantly more hypermethylated in Group 1. In Group 2, HSP70, HSP90 HSF1, HSR1, and eEF1a a were significantly hypomethylated compared to Group 1 and Group 3 (for all genes p<0.001). The HSF1 hypomethylation was negatively correlated with MMSE and positively correlated with depression scores (p=0.03 and p=0.013, respectively). The correlation of eEF1a a with MMSE and depression was the opposite of HSF1 (p<0.001 and p=0.013, respectively). Conclusion: Cell line and autopsy studies indicate that eEF1a a hypermethylation might be one of the main molecules triggering alpha-synuclein aggregation in the pathogenesis of PD. Therefore, eEF1a a may be a molecule that can be used as a peripheral biomarker. The findings supported this idea as it was more hypermethylated in PD patients than in controls, whereas its negative regulator HSF1 was hypomethylated and correlated with the clinic. Furthermore, the worsening of cognitive functions and depression in PD patients may affect methylation levels of chaperone genes in the peripheral blood.
Keywords: Cognitive dysfunction; DNA methylation; eEF1 alpha; heat shock activator complex; Parkinson's disease; Parkinson's disease